Application and systematization of statistical process control in a fruit packaging line - Melo, Diego Jean de; Silva, Laila Alves da; Paiva, Anderson Paulo de; Quinino, Roberto da Costa (Brazilian Journal of Production Engineering, 2022)
Agriculture is one of the most important segments in the world economy, responsible for leveraging the GDP of many countries such as China, Brazil, India and the United States. With such great representation, the development and application of improvement tools in this segment becomes highly relevant. In this sense, this article aims to present the application of Statistical Process Control (SPC) integrated with the concept of Industry 4.0 to reduce process losses in a packaging line of a fruit growing company. Of the tools that make up the CEP, the capacity analysis and the I-MR control chart were integrated into a digital and online system in order to analyze the suitability of the process with the customer’s expectations. The results of the application of the system were the reduction in the loss of packages with weight outside the specification standards, having a reduction of the average of the packaged weight in 8.10%, and deviation from the average of the process to the target of only 0.17% . The process has also become more robust, with a standard deviation reduction of 68.33%. Thus, it is possible to conclude the efficiency of the application of the CEP with a digital system to obtain better results in agricultural processes.